L. WONG - Adaptive Reuse. Extending the Lives of Buildings - Gioeni, Laura (ZARCH, 2021)
Liliane WongAdaptive Reuse. Extending the Lives of BuildingsBasilea: Birkhäuser, 2016. 264 pp. Tapa blanda. Idioma: inglés. 39,95 €ISBN: 978-3038215370